Integrating Advanced Technologies in Education: Empowering Youth for a Sustainable Future through New Literacies - Flogie, Andrej; Hari, Daniel; Bratina, Matevž; Kerneža, Maja; Aberšek, Boris; Zemljak, Dejan (Revija za elementarno izobraževanje, 2025)
The quasi-experimental study explores how contemporary technologies, such as artificial intelligence and humanoid robots, enhance sustainability education for pre-service teachers. The study, involving 112 participants, assessed the effectiveness of these technologies compared to traditional methods in improving sustainability literacy. Pre- and post-tests revealed significant improvements in understanding sustainability concepts, with humanoid robots increasing response variability. Results highlight the technologies’ ability to engage educators in sustainability topics, promoting new literacies critical for addressing environmental challenges.
Keywords: advanced technologies, digital competence, humanoid robots, sustainability education, teacher training.